Analysis of Light‐Emission Polarization Ratio in Deep‐Ultraviolet Light‐Emitting Diodes by Considering Random Alloy Fluctuations with the 3D k·p Method. Issue 2 (14th November 2021) - Shen, Huan-Ting; Chang, Yu-Chieh; Wu, Yuh-Renn
Abstract : For nitride‐based AlGaN light‐emitting diodes, the fluctuations in the potential caused by alloy disorder can relax the compressive strain in the lower Al (higher Ga) composition sites. However, strain in the quantum wells impacts the bandgap and the transverse magnetic/transverse electric (TE) polarization ratio. Herein, the 6 × 6 k·p method combined with a 3D Poisson, drift diffusion, and localization landscape solver is used to study the changes in the polarization ratio due to random alloy fluctuations. The influence of different Al compositions in the buffer layer is studied. The results show that the TM polarization ratio with alloy fluctuations is higher than that without fluctuations. On increasing the Al composition in the buffer layer, the polarization ratio changes from 0.93 to −0.67 when the Al composition changes from 60% to 100%. Abstract : A 3D plot of the conduction band profile distribution of AlGaN‐based ultraViolet C radiation light‐emitting diodes (LEDs) is shown. The random alloy fluctuation is considered where the potential fluctuates with composition and polarization variations.